Pancasila sebagai pilar kesatuan bangsa: Menggali makna identitas nasional dan nasionalisme dalam menjaga keutuhan bangsa - Putri, Dwi Ananda (Maliki Interdisciplinary Journal, 2024)
This article discusses the concept and role of national identity in the context of development and state stability using a quantitative approach or library research method. National identity is a general description of the combination of values, culture and characteristics that characterize a nation. This research examines how national identity is formed, maintained and changes over time and its impact on the unity of the Indonesian nation. Through a deep understanding of national identity, this article provides insight into the complexity between Pancasila, nationalism and religion in the context of globalization and cultural plurality.